ANALISIS EFEKTIFITAS PENGGUNAAN FITUR PREPOPULATED DATA PADA APLIKASI E-FAKTUR DALAM PELAPORAN SPT MASA PAJAK PERTAMBAHAN NILAI DI PT SINERGI ADITMITRA JAYA - Pratiwi, Diah; Pentanurbowo, S (Jurnal Ilmu Administrasi Publik, 2025)
the Prepopulated Data feature in the e-Faktur application to improve efficiency and accuracy in reporting the Periodic VAT Return at PT Sinergi Adimitra Jaya. But tax reporting is often carried out at the deadline due to obstacles such as system errors, external data mismatches, and long internal data validation processes. The purpose of this study is to analyze of the effectiveness of using the Prepopulated Data feature in the e-Faktur application in reporting the Periodic VAT Return at PT Sinergi Adimitra Jaya. The research method used is descriptive qualitative, with data collection by interview, observation and documentation. The results showed that the Prepopulated Data feature was effective in simplifying data filling, reducing input errors, and increasing the efficiency of reporting Periodic VAT Returns at PT Sinergi Adimitra Jaya. The company make internal coordination and more intensive socialization from the Directorate General of Taxes to make tax reporting more accurate efficient and timely.